Open Debate About Knees. (Communications of the ACM, 2010)
The author discusses the concept of a knee in terms of computer program performance, defined as a section of a curve where response times and throughput are optimally balanced. An argument by computer scientist Neil Gunther that such knees are not based on mathematical discontinuities, but merely reflect human preferences, is critiqued.